Smart Hunting Cage for Predatory Animals and Moving Bait for Zoology Researches - Mohammed Ehsan Safi (Engineering and Technology Journal, 2016)
This paper presented an approach to design and implement a control scheme for hunting cages of predatory animals without hurting for scientific researchers or animals. In this paper, laser detection circuit is applied to detect target entering the cage and send signal to microcontroller to lock the two gates of the cage then send signal to alarm user. The bait is used to lure the target mounted on moving robot using ultrasonic sensor to determine the distance between the target and the bait and made it go in the cage.